Avaliação custo-efetividade da utilização de um teste rápido como método alternativo no fluxograma para a detecção de anticorpos anti-HIV - Borges, Cristina Betim (2008)
Even with the advances that have allowed a better understanding of pathogenesis, epidemiology and prevention of infection, approximately 33.2 million people worldwide are suffering from HIV / AIDS. The HIV / AIDS is considered a pandemic, causing a major demographic impact due to the devastating infection among young adults. According to the Organization of the United Nations fighting AIDS (UNAIDS), despite a reduction in the overall number of new infections, this index is still very high, and the sexually transmission still the more frequent form of HIV infection. In order to interrupt transmission efficiently an accurate and fast diagnosis is pivotal. The great majority of diagnostic methods for HIV are based in the detection of antibodies specific to different proteins of the virus or the detection of its genetic material. Therefore delay in obtaining accurate results affects negatively prevention and treatment strategies. In the present study, we examined the effectiveness and cost of a rapid test (Rapid Check) as an alternative method in the serological diagnosis workflow for HIV infection. Three hundred and eight serum samples sent to LACEN-ES between October 2006 and May 2007 were analyzed. Both the Rapid Check and the prototype Tri-line depicted a high degree of concordance (98.97%) compared to other tests used for diagnosis of HIV infection at the LACEN-ES. In parallel, from 16 samples with results considered as "inconclusive" by the normal workflow due to absence or low reactivity of anti-gp41, only 3 out of these 16 were still considered inconclusive after using the Rapid Check. In addition to its efficiency, when cost were considered, rapid tests had the lowest cost/test, and required the shortest time to provide a final result (less than 15 minutes) not requiring additional equipment, accessories or specific infrastructure. Therefore, we believe that rapid tests with performance equal to or greater than the Rapid Check could be used as an alternative method at the Immunofluorescence, thus promoting a reduction in the cost and time of release of results.